Integration of aero-elastic belt into the built environment for low-energy wind harnessing: current status and a case study - Aquino, Angelo I.; Calautit, John Kaiser; Hughes, Ben Richard (Elsevier, 2017)
Low-powered devices are ubiquitous in this modern age especially their application in the urban and built environment. The myriad of low-energy applications extend from wireless sensors, data loggers, transmitters and other small-scale electronics. These devices which operate in the microWatt to milliWatt power range and will play a significant role in the future of smart cities providing power for extended operation with little or no battery dependence. Low energy harvesters such as the aero-elastic belt are suitable for integration with wireless sensors and other small-scale electronic devices and therefore there is a need for studying its optimal installation conditions. In this work, a case study presenting the Computational Fluid Dynamics modelling of a building integrated with aero-elastic belts (electromagnetic transduction type) was presented. The simulation used a gable-roof type building model with a 27° pitch obtained from the literature. The atmospheric boundary layer flow was employed for the simulation of the incident wind. The work investigates the effect of various wind speeds and aero-elastic belt locations on the performance of the device giving insight on the potential for integration of the harvester into the built environment.